2000
DOI: 10.1523/jneurosci.20-24-09290.2000
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Membrane Excitability in Gonadotropin-Releasing Hormone-Secreting Hypothalamic Neurons Regulated by Ca2+-Mobilizing and Adenylyl Cyclase-Coupled Receptors

Abstract: Gonadotropin-releasing hormone (GnRH) secretion from native and immortalized hypothalamic neurons is regulated by endogenous Ca 2ϩ -mobilizing and adenylyl cyclase (AC)-coupled receptors. Activation of both receptor types leads to an increase in action potential firing frequency and a rise in the intracellular pool mimics the receptor-induced activation of I SOC and I SK , leading to an increase in the firing frequency and Ca 2ϩ influx after a transient cessation of electrical activity. However, increasing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 48 publications
2
54
1
Order By: Relevance
“…I naf represents the fast sodium current; I nap a persistent sodium current; I kdr , I kir , and I km denote delayed rectifier, inward rectifier, and M-type potassium currents, respectively; I cal and I cat are L-and T-type calcium currents, respectively. Equations for these currents are taken from LeBeau et al (2000) and Roberts et al (2009) Conventional Hodgkin-Huxley-type models are used for all currents, as follows:…”
Section: Methodsmentioning
confidence: 99%
“…I naf represents the fast sodium current; I nap a persistent sodium current; I kdr , I kir , and I km denote delayed rectifier, inward rectifier, and M-type potassium currents, respectively; I cal and I cat are L-and T-type calcium currents, respectively. Equations for these currents are taken from LeBeau et al (2000) and Roberts et al (2009) Conventional Hodgkin-Huxley-type models are used for all currents, as follows:…”
Section: Methodsmentioning
confidence: 99%
“…In this modulation of membrane excitability, they suggested that the activation of . Furthermore, LeBeau et al (2000) showed the contribution of cAMP-operated inward current to this modulation in GT1 cells. The mechanism of the transient decrease of firing frequency in TN-GnRH neurons (the present study) basically agrees well with these reports.…”
Section: Comparison With the Autoregulation In The Other Putative Gnrmentioning
confidence: 97%
“…SOCCs have been proposed to provide a pacemaker current in other spontaneously firing cells such as neurons 40 and interstitial cells of Cajal. 41 In embryonic pacemaker cells, before functional pacemaker ionic channels have developed, IP 3 -dependent Ca 2ϩ influx through SOCCs has been described and under these circumstances is thought to contribute to pacemaking.…”
Section: Possible Physiological Role Of Socc In Sanmentioning
confidence: 99%